2021
DOI: 10.1177/21582440211047582
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Sources and Negative Effects of Assistant Principals’ Work Intensification?

Abstract: This study sought to provide an understanding of the sources of work intensification and its effects on assistant principals in Turkey, and the coping strategies they use. The participants of this qualitative study were a sample of 18 assistant principals. The current qualitative study was based on semi-structured interviews. Data analysis was performed through descriptive and content analysis. This study revealed that assistant principals had work intensification related to heavy paperwork, a variety of admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Our study revealed that work intensification was strongly correlated with work-related exhaustion, which is in line with the findings of Boxall and Macky [ 67 ]. Previous studies have found that emerging policies and changes in the education system were sources of increasing work intensification pressure on school management staff [ 69 , 70 ]. Under the context of the COVID-19 pandemic, emerging policies and changes in the delivery of education, such as the adoption of online learning, often occurred in response to the severity of the pandemic [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that work intensification was strongly correlated with work-related exhaustion, which is in line with the findings of Boxall and Macky [ 67 ]. Previous studies have found that emerging policies and changes in the education system were sources of increasing work intensification pressure on school management staff [ 69 , 70 ]. Under the context of the COVID-19 pandemic, emerging policies and changes in the delivery of education, such as the adoption of online learning, often occurred in response to the severity of the pandemic [ 71 ].…”
Section: Discussionmentioning
confidence: 99%